Pengenalan Sains (Matematika) dalam Seni Rupa Papua Bersama Anak-Anak Sekolah Dasar Rumah Baca Ayapo: Pengabdian - Sakka Irawan; Agnes Julia Kopeuw; Melissa Aeudia Daullu; Happy Alyzhya Haay; Rosdiana Yoku; Ardian Hangga kelana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service (PKM) activity aims to integrate mathematical concepts with Papuan local wisdom through an ethnomathematics approach. This program was implemented at the Ayapo Reading House, Ayapo Traditional Village, Sentani and involved 30 students consisting of grades 4-6 of Elementary School (SD). The learning method used exploration of traditional Papuan arts such as wood carving (Ohote), bark painting (Khombow), local batik motifs (Hote Hiloi, and Yoniki) to introduce the concept of patterns and symmetry in mathematics. A multisensory approach was applied through clapping activities, rhythmic tapping, and pattern drawing exercises. The results of the activity showed an increase in students' interest in mathematics and their ability to identify patterns and symmetry in Papuan culture. As many as 94% of students became prouder of their cultural heritage after understanding that traditional Papuan art contains complex mathematical concepts. This shows that ethnomathematics learning not only improves numeracy literacy but also strengthens students' cultural identity. This program has successfully proven the effectiveness of local cultural integration in STEM learning, especially for education in 3T (Frontier, Outermost, and Disadvantaged) areas.